2003
DOI: 10.1046/j.1365-2850.2003.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Asylum blues: staff attitudes towards psychiatric nursing in Sarawak, East Malaysia

Abstract: This paper draws upon findings from an ethnographic study of psychiatric service users in a psychiatric institution in Sarawak, East Malaysia. Findings focus primarily on the accounts of nursing staff in relation to attitudes towards psychiatric work and patients. These indicate that despite a rhetoric of decentralized services, a custodial 'asylum' model continues to influence the care of patients at many levels. Negative professional attitudes towards patients lead to issues of both moral and physical contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Our figures were however lower than those found on a recent study on Malaysian medical students which utilised the same scale [ 67 ]. Taken together, it appears that significant stigmatising attitudes towards people with mental illness are prevalent among nurses and future doctors in Malaysia, a finding which is consistent with local and international studies [ 4 , 29 , 31 , 34 ]. Anti-stigma interventions which target HCPs in all areas of healthcare provision, and especially those working in primary care should be carried out to improve mental health services.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Our figures were however lower than those found on a recent study on Malaysian medical students which utilised the same scale [ 67 ]. Taken together, it appears that significant stigmatising attitudes towards people with mental illness are prevalent among nurses and future doctors in Malaysia, a finding which is consistent with local and international studies [ 4 , 29 , 31 , 34 ]. Anti-stigma interventions which target HCPs in all areas of healthcare provision, and especially those working in primary care should be carried out to improve mental health services.…”
Section: Discussionsupporting
confidence: 83%
“…This finding may be explained by the fact that only a small number of nurses reported experiences of negative contact (8%) compared to neutral contact (48%). Another possibility for this finding is that the nurses who classified their interactions as neutral were influenced by cultural beliefs which stigmatised mental illness [ 17 , 29 , 72 ]. For example, two studies found a tendency among the Malaysian public to perceive people with mental illness as dangerous, leading to fear and social distance [ 17 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations